Book Reviews. Issue 3 (1st September 2015) - Sperling, Joy; Lindholm, Christina; Loranger, David; Muratovski, Gjoko; Yoo, Jeong-Ju; Hart, Rachel; Martin, Kathi
Sustainable Fashion: Past, Present, and Future, Jennifer Farley Gordon and Colleen Hill (2015) London, New Delhi, New York and Sydney: Bloomsbury, 237 pp., ISBN h/bk: 978-0-8578-5184-0, p/bk: 978-08578-5185-7Shoes: An Illustrated History, Rebecc a Sh awcross (2014) Bloomsbury: London, 256 pp., ISBN: 9781472531001, h/bk, $40.00Cultural Threads: Transnational Textiles Today, Jessica Hemmings (2015) London, UK: Bloomsbury, 248 pp., ISBN: 9781472530936, p/bk, $47.45Luxury: Fashion, Lifestyle and Excess, Patrizia Calefato (2014) London, New Delhi, New York and Sydney: Bloomsbury, 116 pp., ISBN: 9780857853318, p/bk, £16.19; h/bk, £49.50The Visible Self: Global Persp ectives on Dress, Culture, and Society, Joanne B. Eich er and Sandra Lee Evenson (2015) New York and London: Fairchild Books, 406 pp., ISBN: 97816099018702, p/bk, $115.00Who's Who in Fashion, Price Allford, Holly and Stegemeyer, Anne (2014) 6th ed. London and New York: Fairchild Books, An Imprint of Bloomsbury Publishing Inc., 476 pp., ISBN: 9781609019693, $93.99Fashion and Museums : Theory and Practice, Marie Riegels Melch ior and Birgitta Svensson (eds) (2014) London: Bloomsbury Academic, 210 pp., ISBN: 9781472567932, p/bk, $24.50–$29.85